The effect of bioactive polyphenols from Anacardium occidentaleLinn. leaveson α-Amylase and dipeptidyl peptidase IV activities - Abdullah Thaidi, Nur Imanina; Mat Jusoh, Hanapi; Ghazali, Ahmad Badruddin; Susanti, Deny; Haron, Normah (Chemistry Department, Universitas Gadjah Mada, Indonesia., 2020)
Anacardium occidentaleLinn. (A. occidentaleL.) leaves possess bioactive polyphenols which are associated with antidiabetic potency for the management of type 2 diabetes mellitus (T2DM). In this study, free, soluble ester,and insoluble-bound phenolic fractions from young and mature leaves of A. occidentaleL. were extracted. Subsequently, all fractions were investigated for their inhibitory effect on α-amylase and dipeptidyl peptidase IV (DPPIV) activities. Both free (72.45 ± 3.6%) and soluble ester (83.40 ± 4.7%) phenolic fractions in the mature leaves extracts had significantly demonstrated greater α-amylase inhibitors than the young leaves. Likewise, soluble ester (4.09 ± 0.34 μg/mL) and insoluble-bound (4.87 ± 0.32 μg/mL) phenolic fractions in the mature leaves extracts were significantly more effective in inhibiting DPPIV than the young leaves. As for fractions comparison, insoluble-bound derived from the young leaves extract was a more potent α-amylase inhibitor than free and soluble ester phenolic fractions (p < 0.0001). Besides, soluble ester and insoluble-bound phenolic fractions showed a stronger inhibitor of DPPIV than the free phenolic (p < 0.001), irrespective of the maturity of the leaves. In conclusion, this study showed that A. occidentaleL. extracts possessed antidiabetic properties,which may potentially be used as an alternative treatment for T2DM management.